Nature versus nurture: Structural equation modeling indicates that parental care does not mitigate consequences of poor environmental conditions in Eastern Bluebirds (Sialia sialis) - Madeline Sudnick (Wiley, 2021)
Abstract How organisms respond to variation in environmental conditions and whether behavioral responses can mitigate negative consequences on growth, condition, and other fitness measures are critical to our ability to conserve populations in changing environments. Offspring development is affected by environmental conditions and parental care behavior. When adverse environmental conditions are present, parents may alter behaviors to mitigate the impacts of poor environmental conditions on offspring. We determined whether parental behavior (provisioning rates, attentiveness, and nest temperature) varied in relation to environmental conditions (e.g., food availability and ectoparasites) and whether parental behavior mitigated negative consequences of the environment on their offspring in Eastern Bluebirds (Sialia sialis). We found that offspring on territories with lower food availability had higher hematocrit, and when bird blow flies (Protocalliphora spp.) were present, growth rates were reduced. Parents increased provisioning and nest attendance in response to increased food availability but did not alter behavior in response to parasitism by blow flies. While parents altered behavior in response to resource availability, parents were unable to override the direct effects of negative environmental conditions on offspring growth and hematocrit. Our work highlights the importance of the environment on offspring development and suggests that parents may not be able to sufficiently alter behavior to ameliorate challenging environmental conditions.